Spectrophotometric Determination of Isoptin (Verapamil Hydrochloride) in Pharmaceutical Preparations - Salh, D. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Verapamil Hydrochloride (VH) has been determined spectrophotometrically by using Methyl Orange (MO). In our previous researches MO was used for determination of Mexiletine Hydrochloride [1]. The method was based on complexation between (MO and VH). After shaking and diluting the complex solution with D.W, the pH was adjusted with NaOH and HCl to pH 4. The colored complex formed between VH and the reagents were transferred into separating funnels and extracted using 4.5 ml CH2Cl2 and were shaken for (4 minutes). The extracted organic layer was used for the preparation of the calibration curves for spectrophotometric measurements of VH at 437nm. The blanks were carried out in exactly the same way throughout the whole procedure. Molar absorptivity (Îµ L.mol-1.cm-1), detection limit, limit of linearity (Âµg.ml-1) and r2 were, 1.75*105, 0.009253, 0.08 and 0.993 for (VH-MO) respectively. The method was used with reasonable accuracy and precision for the determination of (VH) in synthetic samples of tablets, capsules and ampoules.